Peningkatan Kompetensi Profesional Guru dalam Penggunaan Google Workspace for Education melalui Workshop - Sumardi Sumardi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
There was a change in the work system and learning system during this pandemic, teachers were required to master information technology in their work and learning. The results of the Principal's supervision show that the professional competence of teachers in mastering technology is still low, it needs to be improved. This research aims to improve professional competence in using Google Workspace for Education and to find out how to improve it through workshops for teachers at SD Negeri Kalikepek. The type of research used is school action research. The object of this research is teacher competency in using Google Workspace for Education, the subject of this research is teachers at SD Negeri Kalikepek. This research was conducted in 2 cycles, each cycle covering planning, implementing, observing, and reflecting. Data collection used observation techniques. The instruments used include participant observation instruments, management observations, and workshop product evaluation. The conclusion of this research is that workshops can improve professional competence in using Google Workspace for Education for teachers at SD Negeri Kalikepek from 14% to 86%; and the implementation of a good workshop must go through the steps of preparation, implementation, monitoring, evaluation, and coherent follow-up.